Reorganization of the management system of the economy as a factor of economic growth of the state - Gapsalamov, Almaz Rafisovich (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
At present time the world economy is in a very difficult position - on the one hand, the economic indicators in many leading countries of the world proceed to fall; on the other hand, scientists cannot find an explanation for this and bring the countries out of a prolonged recession. All these cause the search for new mechanisms of economy functioning. And it does not require to invent something new, rather "to take a dive" into the economic history of individual states and to identify mechanisms of their successful development. The presented study is an attempt to analyze the reasons of the growth of the Soviet economy (USSR), throughout its development, in the context of organizational changes in the management system.